COVID: The Missing Trigger to Start a Remote FIT Course - dos Santos Mamed, Marcelo; Gastaldi, Giacomo (Frontiers in Clinical Diabetes and Healthcare, 2022)
Type 1 diabetes management is a highly demanding task that largely falls on people with diabetes, their family, and their peers. Diabetes self-management education and support aim at increasing knowledge, skills, and confidence to take appropriate diabetes management decisions. The current evidence shows that efficient diabetes self-management relies on person-centered interventions and a team of pluri-disciplinary educators with expertise in diabetes care and education. The irruption of the COVID-19 pandemic has increased diabetes burden and the need to offer remote diabetes self-management education services. The present article offers a perspective about expectations and quality issues related to the implementation of a remote version of the FIT course, a validated structured diabetes management educational program.